2022
DOI: 10.1007/s00289-022-04091-8
|View full text |Cite
|
Sign up to set email alerts
|

An insight into anticancer, antioxidant, antimicrobial, antidiabetic and anti-inflammatory effects of quercetin: a review

Abstract: Flavonoids are present naturally in many fruits and vegetables including onions, apples, tea, cabbage, cauliflower, berries and nuts which provide us with quercetin, a powerful natural antioxidant and cytotoxic compound. Due to antioxidant property, many nutraceuticals and cosmeceuticals products contain quercetin as a major ingredient nowadays. Current review enlightened sources and quercetin’s role as an antioxidant, antimicrobial, antidiabetic, anticancerous and anti-inflammatory agent in medical field duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(88 citation statements)
references
References 54 publications
1
64
0
1
Order By: Relevance
“…QUR is a natural compound of flavonoids, which is not produced in the human body and is found in a variety of food and medicinal plants, such as apples, onions, grapes, cherries, oranges, tomatoes, ginkgo, forsythia, etc. [ 8 , 9 ]. The chemical structure of QUR is C15H10O7 ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…QUR is a natural compound of flavonoids, which is not produced in the human body and is found in a variety of food and medicinal plants, such as apples, onions, grapes, cherries, oranges, tomatoes, ginkgo, forsythia, etc. [ 8 , 9 ]. The chemical structure of QUR is C15H10O7 ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has a fast metabolic rate and a short half-life in blood, and its bioavailability is low [ 14 ]. Modern pharmacological studies have shown that QUR has anti-oxidation, anti-cancer, anti-allergy, anti-inflammation, anti-obesity and neuroprotection properties and shows an inhibition of platelet aggregation, enhancement of mitochondrial synthesis, regulation of intestinal microorganisms and other functions [ 8 , 9 , 15 ]. QUR can intervene in multiple pathological processes of PCOS through multi-target and multi-pathway and is expected to become a new treatment drug for PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin (3,3′,4′,5,7pentahydroxyflavone) is an important flavonoid that possesses antioxidant, antimetastatic, anticancer, anti-inflammatory, and antidiabetic antiulcer properties. 13 Interestingly, this active flavonoid triggers anticancer effects via G1/S transition or G2/M cell cycle arrest and hinders various molecular cascades' activity. However, the usage of Quercetin was limited in the clinical translation due to its poor bioavailability and solubility.…”
Section: Introductionmentioning
confidence: 99%
“…However, the usage of Quercetin was limited in the clinical translation due to its poor bioavailability and solubility. [13][14][15] Hence, the bioactivities of Q-stabilized highly-stable metal nanoparticles such as silver, gold, and bi-metallic were tested to develop a bio-nano colloidal formulation for medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the NCT04468139 trial combined quercetin (500 mg), bromelain (500 mg), vitamin C (1000 mg), and zinc (50 mg) as quadruple therapy for COVID-19 patients. Quercetin, a flavonol component highly present in agro-food byproducts, has a long history as a powerful antioxidant molecule in preventing and combating the oxidative damages of several pro-oxidant agents [ 168 ]. More importantly, previous clinical trials (NCT04578158, NCT04377789, NCT04861298, and NCT04861298) have shown the importance of quercetin supplementation as a preventive or a therapeutic tool for COVID-19 treatment.…”
Section: Role Of Bioactive Compounds In Bee Products In the Managemen...mentioning
confidence: 99%